The Relationship Between Storey of Buildings and Fall Risk - Tsai, Ching-Yao; Lin, En-Sheng; Li, Yang-Tzu; Tung, Tao-Hsin; Chen, Wei-Cheng (Frontiers in Public Health, 2021)
Purpose: This study examined the association between storey of building and fall risk in older adults' residences and residents' level of fear of falling. Methods: The National Health and Ageing Trends Study (NHATS) collected information that would provide an understanding of basic trends people aged 65 years and older. Using a longitudinal survey, the present study employed the first round of NHATS data that was collected in 2011. In the first round, 12,411 participants were enrolled, and 8,077 interviews were completed. The study sample sizes for falling and worry about falling are 6,153 and 6,142, respectively. Results: Unadjusted analysis revealed that storey of building was a risk factor for fall and worry about falling. There was a higher prevalence for fall and worry about falling when subjects lived in single storey of building compared with the subjects live in multi-storey. Logistic regression analysis showed no highly significant between storey of building and the fall/fear of falling. Conclusion: Several clinical factors independently were indicated pertaining to the fall and worry about falling in older adult's residences.